Specific Learning Disorder in Children and Adolescents, a Scoping Review on Motor Impairments and Their Potential Impacts - Mariève Blanchet; Christine Assaiante (MDPI AG, 2022)
Mastering motor skills is important for children to achieve functional mobility and participate in daily activities. Some studies have identified that students with specific learning disorders (SLD) could have impaired motor skills; however, this postulate and the potential impacts remain unclear. The purpose of the scoping review was to evaluate if SLD children have motor impairments and examine the possible factors that could interfere with this assumption. The sub-objective was to investigate the state of knowledge on the lifestyle behavior and physical fitness of participants with SLD and to discuss possible links with their motor skills. Our scoping review included preregistration numbers and the redaction conformed with the PRISMA guidelines. A total of 34 studies published between 1990 and 2022 were identified. The results of our scoping review reflected that students with SLD have poorer motor skills than their peers. These motor impairments are exacerbated by the complexity of the motor activities and the presence of comorbidities. These results support our sub-objective and highlight the link between motor impairments and the sedentary lifestyle behavior of SLDs. This could lead to deteriorating health and motor skills due to a lack of motor experience, meaning that this is not necessarily a comorbidity. This evidence emphasizes the importance of systematic clinical motor assessments and physical activity adaptations.